Putative inhibitory actions of selected medical plants against exonic splicing enhancers - Rashid, Roslina (2020)
A previous study had demonstrated the successful use of isodiospyrin as an inhibitor of splicing factor and the use of a small-molecule compound as exon skipping inducer. Inhibition of serine and arginine-rich (SR) protein using isodiospyrin and their homolog results in exon skipping and indirectly restore the reading frame and protein product. Creating a novel minigene model can be used for studying the complexity of the splicing mechanism, potentially translatable into the identification of therapeutic targets in various related other conditions, such as Duchenne Muscular Dystrophy where the Dystrophin gene is affected. The objective of this study was to determine the inhibitory actions of isodiospyrin and isodiospyrin homolog of selected medicinal plant extracts for inducing skipping in the designed minigene against exonic splicing enhancers. Exonic splicing enhancers of dystrophin minigene was identified using ESEfinder 3.0 software. There are two subtypes of minigene which are genuine minigene and artificial minigene. Genuine minigene includes Gen-Ex45, Gen-Ex 51 and Gen-Ex53 while artificial minigenes with specific exonic splicing enhancers (ESE) are Art-SF2/ASF, Art-Sc35, Art-SRp40, Art-SRp55 and Art-NO ESE. All minigenes were constructed before being subjected to the cloning process and targeted minigenes were validated using sequencing before to transfection into the HEK-293 cell line for splicing assay. The assay was again validated using 2 methods which are luciferase assay by the fluorescent signal and another method by the presence of targeted size band after reverse transcriptase-polymerase chain reaction (RT-PCR) and were then confirmed by sequencing analysis. Six extracts from 5 plants similar to isodiospyrin homolog were screened using NADI software. Direct sequencing further validated the absence of exon after compounds exposure to all minigene, results showed no skipping in all genuine minigene, different with artificial minigene which showed all skippings based on the RT-PCR results. After luciferase analyses, their skipping values were still far from mock minigene (standard skipping) which showed a higher threshold indicating that no skipping occurred and that luciferase assay was more sensitive than RT-PCR. Based on the result obtained, it was proven that fewer ESE sequences in the exon are unable to retain exon. Also, there was a higher potential of skipping to occur if there are few ESE in the sequence, the presence of a silencer motif as well as when that sequence consists of positive splicing potential value. Five of the compounds were shown significantly to induce skipping after exposure to the Art-SRp55 and one of each Art-SC35 and Art-SRp40, while no compounds showed significant skipping after exposure to the Art-SF2/ASF. However, it was shown that the skipping level was not as much as that which occurred in the mock minigene that acted as a skipping standard. Interestingly, isodiospryin showed to have a high tendency to become ESE skipper when exposed to the Art- SRp40 minigene, because it showed a significant skipping value (p= 0.049) although with the presence of silencer motif 1 and higher SP value. In a conclusion, isodiopsyrin and its homologs might have shown the capacity to induce skipping, although in an ESE-specific manner, even with or without the presence of silencer motif and hnRNP A1. This approach may provide a view to further study ESE on the disease-related conditions.